Transfirm Organization View - Nobuo TAKAHASHI (Annals of Business Administrative Science, 2014)
In modern day Japan, an “organization” often comprises multiple, legally separate firms, although it appears as a single organization to customers and external users and may actually operate as one organization. The concept of an “organization” differs from that of a “firm.” The organization is a network or system functioning in practice, whereas the institution of a firm defines the boundary or partitions off a part of the organization by nature. Acknowledging that firms and organizations are different concepts significantly enhances our understanding and conception of the everyday scene of multiple firms functioning as one organization. Theories based on such a way of viewing organizations and firms are called “transfirm organization theories.” Theories on keiretsu corporate affiliation or supplier system, architecture-based interfirm specialization, value networks, Japanese industrial agglomeration, and transnational companies are a few examples. Transfirm organizations are created for economic reasons; however, transfirm organization theories are not concerned with the reasons to create transfirm organizations, but rather with the performance of the transfirm organization as a whole.